ТРУДОВА МІГРАЦІЯ ЗА КОРДОН У СУЧАСНИХ УМОВАХ ТРАНСФОРМАЦІЇ ЕКОНОМІКИ УКРАЇНИ - Todoruk, Sergy; Nykyforak, Valentina; Antochova, Irina (My University, 2019)
Статтю присвячено проблемам трудової міграції: визначено вікові групи короткострокових і довгострокових трудових мігрантів, динаміка співвідношення їх за основними регіонами призначення, рівень освіти українських мігрантів, сектори зайнятості за статтю, цілі заощаджень українських довгострокових трудових мігрантів. Проаналізовано рівень заробітної плати в країнах ЄС, середній особистий дохід довгострокових мігрантів чоловічої і жіночої статі за рівнем зайнятості, обсяги приватних грошових переказів в Україну, їх вплив на розвиток економіки України та на рівень доходів домогосподарств. Охарактеризовані чинники української трудової міграції та визначена її головна причина. Розкрито трудові правові аспекти українських працівників-мігрантів, та їх соціальний захист. Досліджено зміни у структурі трудової міграції з України за останні роки, зазначено, що збільшується обсяг довгострокової міграції; до міграції вдається більше чоловіків, що пов'язано не лише із потребами ринку праці країн призначення (будівництво, транспорт), а й виїздом за кордон унаслідок воєнних дій на сході України; збільшується частка молоді, жінок, мешканців міст, вихідців із північної, центральної та східної України. Обґрунтовано, що збільшення масштабів та тривалості перебування мігрантів за кордоном невідворотно приведе до послаблення їхніх в'язків з Батьківщиною, остаточної втрати країною частини її трудового та інтелектуального потенціалу. Евентуальний дефіцит працівників може стати гальмом розвитку економіки, а також найбільш активних молодих та освічених осіб — демократичних перетворень в Україні. Запропоновано шляхи розв'язання проблем трудової міграції на сучасному етапі розвитку України, по-перше, підтримати модель циркулярної міграції, що склалася стихійно, з надією на можливе остаточне повернення мігрантів на Батьківщину, по-друге, забезпечити легальне працевлаштування українських мігрантів за кордоном, недискримінацію та дотримання їхніх прав, зокрема у сфері соціального забезпечення.
LABOUR MIGRATION ABROAD IN THE CURRENT CONDITIONS OF TRANSFORMATION OF UKRAINE'S ECONOMY
The article deals with the problems of labour migration: there being determined the age groups of short-term and long-term migrant workers, dynamics of their correlation according to the main regions of destination, the education level of Ukrainian migrants, sectors of employment depending on gender, and the goals of savings of Ukrainian long-term migrant workers. The article analyzes the level of salaries in the EU countries, the average personal income of long-term male and female migrants in terms of employment level, the volume of private money transfers to Ukraine, their impact on the development of the Ukrainian economy and on household income level. The factors of Ukrainian labor migration are characterized and its main reason is determined. The labour legal aspects of Ukrainian migrant workers and their social protection are explained. Changes in the structure of labor migration from Ukraine in recent years have been researched, it is indicated that the volume of longterm migration is increasing; it is the male part of population that migrate more, which is related not only to the needs of the labour market of the countries of destination (construction, transport), but also travelling abroad as a result of hostilities in eastern Ukraine; the proportion of young people, women, city dwellers, immigrants from northern, central and eastern Ukraine is increasing. It is substantiated that increase in the scale and duration of migrants' stay abroad will inevitably lead to weakening their relations with the Motherland, the ultimate loss of the country's labour and intellectual potential to some extent. The eventual shortage of workers can hinder the development of the economy, as well as the democratic transformations in Ukraine. The ways of solving the problems of labor migration at the present stage of Ukraine's development are proposed, firstly, to support the model of circular migration which appeared unintionally, expecting possible and final return of migrants to the Motherland, and, secondly, to ensure legal employment of Ukrainian migrants abroad, non-discrimination and respecting their rights, in particular in the field of social security.
Keywords: трудова міграція; міграційна політика; стратегічне бачення міграційного ресурсу; стратегія регулювання міграційних потоків; модель циркулярної міграції; моніторинг міграційної ситуації; добровільне пенсійне страхування мігрантів; labour migration; migration policy; strategic vision of migration resource; strategy of migration flow management; migration situation monitoring; voluntary pension insurance of migrants